The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1678-7757-2018-0357
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and optical properties of conventional restorative glass-ionomer cements - a systematic review

Abstract: Objectives To perform a systematic review of test methodologies on conventional restorative glass-ionomer cement (GIC) materials for mechanical and optical properties to compare the results between different GICs. Material and Methods Screening of titles and abstracts, data extraction, and quality assessments of full-texts were conducted in search for in vitro studies on conventional GICs that follow the relevant specifications of ISO standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
0
28
0
6
Order By: Relevance
“…Many elderly patients have an adverse, highly acidic oral environment, which could be due to salivary gland side effects of prescribed or over-the-counter medicines, systemic disease (particularly diabetes mellitus and subclinical dehydration), or various forms of gastric reflux [ 1 , 2 ]. GIC restorations can act as a biomimetic dentine replacement, having similar thermal expansion properties to natural tooth structures, or as a bulk restorative for use in sites with low compressive loads [ 3 ]. Their common applications are for restoring carious lesions located on root surfaces, or interdentally (using the sandwich technique, where they are overlaid with a resin composite material).…”
Section: Introductionmentioning
confidence: 99%
“…Many elderly patients have an adverse, highly acidic oral environment, which could be due to salivary gland side effects of prescribed or over-the-counter medicines, systemic disease (particularly diabetes mellitus and subclinical dehydration), or various forms of gastric reflux [ 1 , 2 ]. GIC restorations can act as a biomimetic dentine replacement, having similar thermal expansion properties to natural tooth structures, or as a bulk restorative for use in sites with low compressive loads [ 3 ]. Their common applications are for restoring carious lesions located on root surfaces, or interdentally (using the sandwich technique, where they are overlaid with a resin composite material).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no study in the literature followed exactly the ISO requirements, preventing any chance of comparison among outcomes. 17 The DTS and KH values have been accepted for clinical application for most GICs tested in this study; the FS results point to a need for enhancement of some conventional GICs. The GICs with highest FS values were GL2, EF, GL9 and IS.…”
Section: Discussionmentioning
confidence: 68%
“…16 Many studies test and compare the CS among different conventional GICs, however it is impossible to compare them due to differences in the methodological approaches of most studies reported. 17 The ISO is responsible for developing and publishing international standards in order to ensure quality, safety and efficiency of products, services and systems around the globe. 18 However, most researchers do not completely follow these specifications, altering some features such as the specimen's dimensions, storage and testing time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the color stability offered by these reinforced glass ionomer cements may not, in their current form, be adequate for their use as anterior esthetic restorations. International Journal of Dentistry e relationship between the nature of the reinforcing particle, the powder liquid ratio, and solubility of the glass ionomer cement has been extensively documented in the literature [2,3,6,21]. One of the suggested advantages of using nanoparticles is that, given their low size, it is possible to maintain suggested powder liquid ratios and still achieve a sustainable aluminofluorosilicate gel matrix [6].…”
Section: Discussionmentioning
confidence: 99%